Long-term survival and virulence of Mycobacterium leprae in amoebal cysts. - William H Wheat; Amy L Casali; Vincent Thomas; John S Spencer; Ramanuj Lahiri; Diana L Williams; Gerald E McDonnell; Mercedes Gonzalez-Juarrero; Patrick J Brennan; Mary Jackson (Public Library of Science (PLoS), 2014)
Leprosy is a curable neglected disease of humans caused by Mycobacterium leprae that affects the skin and peripheral nerves and manifests clinically in various forms ranging from self-resolving, tuberculoid leprosy to lepromatous leprosy having significant pathology with ensuing disfiguration disability and social stigma. Despite the global success of multi-drug therapy (MDT), incidences of clinical leprosy have been observed in individuals with no apparent exposure to other cases, suggestive of possible non-human sources of the bacteria. In this study we show that common free-living amoebae (FLA) can phagocytose M. leprae, and allow the bacillus to remain viable for up to 8 months within amoebic cysts. Viable bacilli were extracted from separate encysted cocultures comprising three common Acanthamoeba spp.: A. lenticulata, A. castellanii, and A. polyphaga and two strains of Hartmannella vermiformis. Trophozoites of these common FLA take up M. leprae by phagocytosis. M. leprae from infected trophozoites induced to encyst for long-term storage of the bacilli emerged viable by assessment of membrane integrity. The majority (80%) of mice that were injected with bacilli extracted from 35 day cocultures of encysted/excysted A. castellanii and A. polyphaga showed lesion development that was similar to mice challenged with fresh M. leprae from passage mice albeit at a slower initial rate. Mice challenged with coculture-extracted bacilli showed evidence of acid-fast bacteria and positive PCR signal for M. leprae. These data support the conclusion that M. leprae can remain viable long-term in environmentally ubiquitous FLA and retain virulence as assessed in the nu/nu mouse model. Additionally, this work supports the idea that M. leprae might be sustained in the environment between hosts in FLA and such residence in FLA may provide a macrophage-like niche contributing to the higher-than-expected rate of leprosy transmission despite a significant decrease in human reservoirs due to MDT.